The relationship between work values, organizational commitment and job performance among executives in Malaysia - Zawawi, Dahlia (2003)
Areas such as work values, organizational commitment, and job performance has been widely researched for the past years. The main purpose of this study was to identify the relationships between work values, organizational commitment, and job performance among managers in Malaysia. In addition, the study was also meant to identify the possible variations between selected demographic variables with work values, organizational commitment, and job performance. Two h undred thirteen (213) executives from 48 organizations participated in this research. The instruments used were Work Values Scale (Elizur, 1996), Organizational Commitment Scale (Meyer and Allen, 1990), and Job Performance Scale (Suliman, 2001). Statistical analyses used for the study included the Pearson Correlation, Independent t-test, one-way AN OVA, multiple regression, and path analysis.The analyses of data revealed significant relationships between work values and organizational commitment, and work values and job performance. Indirect relationship was seen between organizational commitment to job performance through work values. Race, academic qualification, division, and monthly salary were found to be related to work values. Age, marital status, and academic qualification were found to be related to organizational commitment. Finally, working experience were related to job performance. This study was able to prove the hypotheses proposed and was able to provide new support on the existing theories. It also managed to add new information and understanding on the organizational practices in Malaysia.